High‐Contrast Fluorescence Diagnosis of Cancer Cells/Tissues Based on β‐Lapachone‐Triggered ROS Amplification Specific in Cancer Cells. (29th April 2021) - Liu, Jing; Liu, Mengxing; Zhang, Hongxing; Guo, Wei
Abstract: Discrimination of cancer cells/tissues from normal ones is of critical importance for early diagnosis and treatment of cancers. Herein, we present a new strategy for high‐contrast fluorescence diagnosis of cancer cells/tissues based on β‐Lapachone (β‐Lap, an anticancer agent) triggered ROS (reactive oxygen species) amplification specific in cancer cells/tissues. With the strategy, a wide range of cancer cells/tissues, including surgical tissue specimens harvested from patients, were distinguished from normal ones by using a combination of β‐Lap and a Si‐rhodamine‐based NIR fluorescent ROS probe PSiR3 developed in this work with average tumor‐to‐normal (T/N) ratios up to 15 in cell level and 24 in tissue level, far exceeding the clinically acceptable threshold of 2.0. What's more, the strategy allowed the fluorescence discrimination of tumor tissues from inflammatory ones based on whether a marked fluorescence enhancement could be induced when treated with PSiR3 and β‐Lap/PSiR3 combination, respectively. Abstract : Based on β‐Lapachone‐triggered ROS amplification specific in cancer cells/tissues, a wide range of cancer cells/tissues, including surgical tissue specimens harvested from patients, were distinguished from normal ones by using a combination of β‐Lap and a Si‐rhodamine‐based NIR fluorescent ROS probe with average tumor‐to‐normal (T/N) ratios up to 15 in cell level and 24 in tissue level, far exceeding the clinically acceptable threshold of 2.0.